DIALOG ANTARAGAMA SEBAGAI SARANA MEMBANGUN POLITIK DAMAI ANTAR UMAT BERAGAMA JELANG PEMILU TAHUN 2024 (Tinjauan atas Filsafat Politik Eko Armada Riyanto) - markus putra dusma (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2022)
The focus of this essay is on interreligious dialogue as an effort to build peaceful politics ahead of the 2024 general election. The purpose of this paper is to examine religious life in Indonesia. The view of the majority-minority often triggers unhealthy political problems. In other words, religion is often a powerful weapon to bring down political opponents unfairly and humanely. Seeing the reality of the vulnerability of religion being used as an unhealthy political tool, interreligious dialogue becomes something urgent, especially before the elections in the next two years. Interreligious dialogue needs to be built from now on so that the atmosphere ahead of the elections in the next 2 years is better than before. In this article, we will also use a quantitative method by using the literature as a reference. The finding from this paper is that religious issues are very influential on politics in Indonesia, so there needs to be interreligious dialogue in order to create peaceful politics, especially ahead of the 2024 elections.